The impact of competitive strategies and market concentration on earnings smoothing in the banking sector: Evidence from 10 Iranian Banks - Zahra Mojdeh; Zabihollah Taheri (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
Purpose- This study aims to examine the impact of competitive strategies and market concentration on earnings smoothing behavior in the Iranian banking sector, addressing a gap in the literature by simultaneously investigating the effects of banking competition and market concentration on earnings smoothing within an emerging market context. Design/methodology/approach- The study uses panel data from 10 banks listed on the Tehran Stock Exchange over the period 2014–2023. The dynamic panel Generalized Method of Moments (GMM) estimator is applied to control for endogeneity, autocorrelation, and unobserved heterogeneity. Earnings smoothing is measured using loan loss provisions, banking competition is captured through the Panzar–Rosse H-statistic, and market concentration is measured by the asset share of the five largest banks. Findings- The empirical results reveal that both banking competition and market concentration have a positive and significant effect on earnings smoothing behavior. Banks operating in highly competitive and concentrated markets tend to stabilize reported earnings in order to preserve investor confidence, reduce perceived financial risk, and maintain market reputation. However, the moderating role of earnings before provisions and taxes is found to be statistically insignificant. Originality/value- This study contributes to the literature on banking behavior, earnings management, and industrial organization by providing novel empirical evidence from the Iranian banking industry as a representative emerging banking system. The findings also offer practical implications for regulators and policymakers seeking to enhance financial transparency, supervisory monitoring, and governance quality in banking institutions.